THE ROLE OF LEADERSHIP AND STRATEGIC MANAGEMENT IN ENHANCING THE QUALITY OF ISLAMIC EDUCATIONAL INSTITUTIONS - Noviyanti, Shobihatul Fitroh; Romzi, Moh. (JURNAL SELAKSA MAKNA, 2025)
This study aims to determine the use of the Google Form application as a learning evaluation tool for Islamic Religious Education weekend students of STIT Madani Yogyakarta. Using a qualitative approach, data were collected through literature study, observation, interviews, and literature studies. Data analysis was performed using the Miles and Huberman model. The results showed that the use of Google Forms provides convenience for students and lecturers in the assessment process, especially in weekend classes that rely more on technology. This research provides an overview of the importance of technology integration in learning to improve the efficiency and effectiveness of the evaluation process. It is hoped that the results of this research can make a positive contribution to the development of online learning assessment methods in educational institutions.   Penelitian ini bertujuan untuk mengetahui pemanfaatan aplikasi Google Form sebagai alat evaluasi pembelajaran Pendidikan Agama Islam Mahasiswa kelas weekend STIT Madani Yogyakarta. Dengan menggunakan pendekatan kualitatif, data dikumpulkan melalui studi pustaka, observasi, wawancara, dan studi literatur. Analisis data dilakukan menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa penggunaan Google Form memberikan kemudahan bagi mahasiswa dan dosen dalam proses penilaian, terutama pada kelas weekend yang lebih mengandalkan teknologi. Penelitian ini memberikan gambaran tentang pentingnya integrasi teknologi dalam pembelajaran untuk meningkatkan efisiensi dan efektivitas proses evaluasi. Diharapkan hasil penelitian ini dapat memberikan kontribusi positif dalam pengembangan metode penilaian pembelajaran daring di institusi pendidikan.